THE EFFECT OF LANGUAGE COMMONALITY ON TRADE: A STUDY OF THE TEN MOST INFLUENTIAL GLOBAL LANGUAGES - Ly, A.; Esperança, J.; Amaral-Baptista, M.; Pereira, I. (European International Business Academy (EIBA) - 40th Annual Conference - The Future of Global Organising, 2014)
Language has been a key variable in extended gravity models focussed on foreign trade. This study extends previous research of common language network externalities by measuring its impact on bilateral trade, from the point of view of the ten most global languages in the world. We analyse a total of 58 countries in which the 10 global languages are predominant, according to the Ethnologue and the Calvet Barometer classifications. Our findings provide evidence that language commonality has a significant impact on bilateral trade, albeit lower that than the hitherto more researched effect of geographic distance, therefore playing a significant role on the definition of foreign market entry strategies.